Amos Oz : writer, activist, icon - Alter, Robert (Jewish lives (New Haven, Conn.), 2023)
"Amos Oz (1939-2018) was one of Israel's most prolific and prominent writers, as well as a regular contender for the Nobel Prize for Literature. He was the author of dozens of novels, essay collections, and novellas written between 1965 and shortly before his death. In this first published biography of Oz, the celebrated translator, literary critic, and biblical scholar Robert Alter explores Oz's relationship with his family, beginning with the suicide of his mother, Fania Klausner, when he was twelve years old, and goes on to review his time in Kibbutz Hulda, which he entered at fourteen following his separation from his father, Arieh Klausner; his family's right-wing Zionism; his writing career; his activism in support of a pluralistic Israel; and his work as an international lecturer. In examining Oz's life and work, Alter brings together testimony from Oz and his circle, as well as close readings of his central works, to present the inner world and public persona of Amos Oz.--Dust jacket.